(untitled) (Международный научный журнал «Инженер», 2026)
This study examines the issues of ensuring road traffic safety in the public transport system of Tashkent city and creating a convenient and safe environment for pedestrians. It also analyzes the directions for the comprehensive development of public transport, the provision of high-quality and safe transport services to passengers, and the improvement of transport infrastructure. The paper highlights modern methods and effective solutions for enhancing traffic safety in public transport.